Combined electro-pneumatic braking matching control for smooth operation of the heavy-haul train - MA Zhiqiang; WANG Junyu; WEI Mi; WANG Qingyuan (机车电传动)
Heavy-haul trains need to be braked in cycles when running on long and steep downslopes, which causes great challenges for drivers and brings huge influences to the safe and smooth operation of the trains. In the current study, a multi-objective optimal operation model was established for heavy-haul trains firstly, considering the dynamic process in the application of air braking force, and the constraints due to the train operation environment and vehicle mechanical characteristics, and then was solved by the quadratic programming algorithm. Since the air braking model can hardly be linearly approximated, the air braking force was incorporated into the optimization model as a kind of train known control force, taking advantage of the consistent main characteristics of the modeled speed curve, resulting in the electro-pneumatic braking control decoupled spatially and temporally. Moreover, an iterative algorithm was designed to fit the air braking force with the optimized speed curve. Finally, the operation criteria for heavy-haul trains on long and steep downslopes were quantified and incorporated into the model as the specific constraints parameters for simulative study, and the results were compared with the measured operation data. The comparison results demonstrate that the proposed algorithm can achieve safe and steady operation of heavy haul trains by reducing coupler force.